The influence of 71Ag-28Cu-1Mg filler alloy on microstructure and properties of spot brazed Titanium/Nickel joint - Hussain, Zuhailawati; Alaa Muhsin, Saeed; Ahmad Badri, Ismail; Tadashi, Ariga (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.